Effects of performance feedback valence on perceptions of invested mental effort. (October 2017) - Raaijmakers, Steven F.; Baars, Martine; Schaap, Lydia; Paas, Fred; van Gog, Tamara
Abstract: We investigated whether the valence of performance feedback provided after a task, would affect participants' perceptions of how much mental effort they invested in that same task. In three experiments, we presented participants with problem-solving tasks and manipulated the presence and valence of feedback between conditions (no, positive, or negative feedback valence), prior to asking them to rate how much mental effort they invested in solving that problem. Across the three experiments–with different problem-solving tasks and participant populations–we found that subjective ratings of effort investment were significantly higher after negative than after positive feedback; ratings given without feedback fell in between. These findings show that feedback valence alters perceived effort investment (possibly via task perceptions or affect), which can be problematic when effort is measured as an indicator of cognitive load. Therefore, it seems advisable to measure mental effort directly after each task, before giving feedback on performance. Highlights: 3 experiments showed that feedback valence affected perceptions of invested effort. Perceived mental effort was higher after negative than after positive feedback. We replicated that overall effort ratings were higher than task-specific ratings. Overall and task-specific effort ratings were both affected by feedback valence. Thus, mental effort is best measured directly after each task, before giving feedback.